2015
DOI: 10.1590/0103-8478cr20141160
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and quality characteristics of five apples cultivars

Abstract: '-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS). 'GoldRush' had the highest total phenolic compared to the other four cultivars. Additionally, 'GoldRush' had slightly higher, DPPH activity followed by 'Crimson Crisp' and 'Wine Crisp'. 'GoldRush' and 'Crimson Crisp'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 13 publications
2
10
1
3
Order By: Relevance
“…However, changes in total organic acid content in response to 1-MCP treatment or storage duration were different from changes in titratable acidity or pH (Table 1). Previously, we reported different organic content among these five apple cultivars [26]. At harvest, we found that the total organic acid content was the lowest in "Pixie Crunch" [26].…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…However, changes in total organic acid content in response to 1-MCP treatment or storage duration were different from changes in titratable acidity or pH (Table 1). Previously, we reported different organic content among these five apple cultivars [26]. At harvest, we found that the total organic acid content was the lowest in "Pixie Crunch" [26].…”
Section: Resultsmentioning
confidence: 60%
“…Previously, we reported different organic content among these five apple cultivars [26]. At harvest, we found that the total organic acid content was the lowest in "Pixie Crunch" [26]. After storage, total organic acid content was highest in "GoldRush" and lowest in "Pixie Crunch" (Figure 2).…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations